Budesonide use and misuse in sports: Elimination profiles of budesonide and metabolites after intranasal, high‐dose inhaled and oral administrations. Issue 5 (9th August 2019) - Coll, Sergi; Monfort, Núria; Matabosch, Xavier; Papakonstantinou, Katerina; Pérez‐Mañá, Clara; Mateus, Julian A.; Ventura, Rosa
Abstract: Budesonide (BUD) is a glucocorticoid (GC) widely used in therapeutics. In sports, the World Anti‐doping Agency (WADA) controls the use of GCs, and WADA‐accredited laboratories use a reporting level of 30 ng/mL for 6β‐hydroxy‐budesonide (6βOHBUD) to detect the systemic administration of BUD. In the present work, we examined the urinary excretion profile of 6βOHBUD, BUD, and 16α‐hydroxy‐prednisolone (16αOHPRED) after intranasal (INT), inhaled (INH) (at high doses) and oral administrations in male and female volunteers. BUD was administered to healthy volunteers using INT route (256 μg/day for three days, n  = 4 males and 4 females), INH route (800 μg/day for three days, n = 4 males and 4 females, and 1600 μg/day for three days, n = 4 males) or oral route (3 mg, n  = 8 females). Urine samples were collected before and after administration at different time periods, and were analyzed by liquid chromatography–tandem mass spectrometry. 6βOHBUD and BUD concentrations were very low after INT treatment (0.0–7.1 and 0.0–8.1 ng/mL, respectively), and higher after INH treatments (0.0–35.4 and 0.0–48.3 ng/mL, respectively). For 16αOHPRED, elevated concentrations were detected after INT and INH treatments (2.6–66.4 and 3.4–426.5 ng/mL, respectively). Concentrations obtained following oral administration were higher than after therapeutic administrations (2.8–80.6, 1.5–36.1, and 10.4–532.2 ng/mL for 6βOHBUD, BUD, and 16αOHPRED, respectively). After all administrations, concentrations were higher in males than in females. Results demonstrated that 6βOHBUD is the best discriminatory marker and a reporting level of 40 ng/mL was found to be the best criterion to distinguish allowed from forbidden administrations of BUD. Abstract : 6β‐hydroxy‐budesonide (6βOHBUD) is the best marker to detect the systemic administration of budesonide (BUD) in sports. The best criterion to distinguish between allowed and forbidden BUD administrations is a reporting level of 40 ng/mL for 6βOHBUD.